Information and Communications Technology-Based Interventions Targeting Patient Empowerment: Framework Development - Karni, Liran; Dalal, Koustuv; Memedi, Mevludin; Kalra, Dipak; Klein, Gunnar Oskar (JMIR Publications, 2020)
BackgroundEmpowerment of patients is often an explicit goal of various information and communications technology (ICT) (electronic, digital) interventions where the patients themselves use ICT tools via the internet. Although several models of empowerment exist, a comprehensive and pragmatic framework is lacking for the development of such interventions. ObjectiveThis study proposes a framework for digital interventions aiming to empower patients that includes a methodology that links objectives, strategies, and evaluation. MethodsThis study is based on a literature review and iterated expert discussions including a focus group to formulate the proposed model. Our model is based on a review of various models of empowerment and models of technology intervention. ResultsOur framework includes the core characteristics of the empowerment concept (control, psychological coping, self-efficacy, understanding, legitimacy, and support) as well as a set of empowerment consequences: expressed patient perceptions, behavior, clinical outcomes, and health systems effects. The framework for designing interventions includes strategies to achieve empowerment goals using different ICT services. Finally, the intervention model can be used to define project evaluations where the aim is to demonstrate empowerment. The study also included example indicators and associated measurement instruments. ConclusionsThis framework, which includes definitions, can be useful for the design and evaluation of digital interventions targeting patient empowerment and assist in the development of methods to measure results in this dimension. Further evaluation in the form of interventional studies will be needed to assess the generalizability of the model.